Electromagnetic flux modelling of AC field over planar microarray dot electrodes used in rapid dielectrophoretic lab-on-chip device / Aizreena Azaman - Aizreena , Azaman (2012)
This research presents a simulation procedure to determine electromagnetic flux produced by planar microarray electrode used in dielectrophoretic lab-on-device. Recently, dielectrophoretic lab-on-device was a useful technique that offers a simple microarray electrode for sorting and manipulating particles. Here, the finite element method (FEM) (COMSOL package) has been employed to model and simulate this model. The electrode model was developed by using three different conductive materials such as copper, gold and indium tin oxide (ITO). Based on Clausius-Massotti factor, frequency, conductivity and permittivity of particles and conductive medium play an importance role in the production of dielectrophoresis force. Thus, in order to simulate and determine the production of electromagnetic field, this microarray electrode was applied with different frequencies values which are 50Hz, 100Hz, 1 KHz, 50 KHz and 500 KHz; and different conductive medium such as distilled water, air at 1 atmosphere (atm) and yeast solution. Statistical analysis made based on the simulation result has shown that copper produced a wide range of electromagnetic flux density compared with other 2 materials. Besides, different conductive medium applied did not bring any changes towards the electromagnetic flux density produced.